Synthesis of Nickel Ferrite NiFe2O4 Nanoparticles/PVA composite and studying Its electric properties - Ibrahim F. waheed; Emaad T. Bakir; Sabah M. Ali (Tikrit Journal of Pure Science, 2023)
In this work focused on preparing Nickel Ferrite NiFe2O4 Nanoparticles (NFNPs) which prepared  by Sol-Gel Auto-Combustion Method. Incorporating (NFNPs) in PVA afforded NFNPs/PVA composites with different weight of NFNPs.  the NFNPs /PVA composite and  pure PVA were identified by different techniques, FTIR